Development of Flipbook Learning Media Based on the Pancasila Student Profile Strengthening Project (P5) at SDN Sumber Agung - Wafiq Fashohati Rozanah; Etty Pratiwi; Ramanata Disurya (Global Action and Education for Society, 2025)
This study aimed to develop a digital flipbook learning media based on the Strengthening the Profile of Pancasila Students Project (P5) with the theme of Sustainable Lifestyle for fourth-grade students at SDN Sumber Agung. The background of this research was based on the lack of innovative learning media and the low focus and understanding of students regarding P5 material. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The flipbook learning media was developed using Canva and Heyzine applications to present interactive and engaging content. Validation was conducted by subject matter experts, media experts, and language experts. Trials were carried out through student responses in small and large groups. The results showed that the developed flipbook media reached a level of validity and practicality, with an average validation score of 84.13%, categorized as “valid,” and an overall average practicality score of 88.92%, categorized as “very practical.” Therefore, this flipbook media was deemed suitable for use as a learning medium that supports the implementation of the Strengthening the Profile of Pancasila Students Project (P5) in elementary schools.